IMPLEMENTATION OF ARABIC LEARNING CURRICULUM FOR GRADE VIII AT MTS DARUL ULUM: AN INTERDISCIPLINARY STUDY IN ARABIC EDUCATION - Juliana, Rina; Ika, Hartika; Nurfitriani, Siti; Salma, Madian Fitri (Kitaba, 2024)
This study is prompted by the pivotal role of the curriculum in shaping Arabic language learning outcomes, necessitating its continuous refinement to align with educational objectives. Employing a qualitative approach with a descriptive research design, the research delves into the Arabic language curriculum for eighth-grade students at MTs Darul Ulum Beraim. The primary objective is to evaluate the curriculum's components, including objectives, content, instructional methods, and assessment strategies. Findings underscore a gap in the curriculum's focus on fostering interactive communication skills, both orally and in writing, with current materials primarily centered on vocabulary and texts related to personal experiences. Consequently, there is a pressing need to revamp the curriculum to prioritize comprehensive language proficiency development, facilitating effective communication in various contexts. This study advocates for curriculum enhancements aimed at equipping students with robust linguistic skills vital for their academic and real-world success in Arabic language proficiency